Strategic and experiential areas of emotional intelligence - Acuña Gil, Maritza (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research work established the degree of correlation between the emotional aptitudes of the strategic and experiential areas of emotional intelligence in undergraduate students in early childhood education of a Colombian Private University Corporation. The quantitative study was based on the MSCEIT instrument as an information collection instrument. The reciprocal incidence of the variables and a positive correlation between the strategic and experiential areas that are indicated in the emotional aptitudes of the sample (130 students) were identified.